STRATEGI PEMASARAN PRODUK ASURANSI SYARIAH DALAM MENARIK MINAT GENERASI MILENIAL MELALUI MEDIA SOSIAL - Dea Salsabila; Fatimah Nainggolan; Siti Nurlina Nasution; Nur Hayati Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2026)
In the current digital era, sharia insurance product marketing strategies need to be adapted to the preferences and behavior of the millennial generation who tend to be active on social media. This research aims to analyze marketing strategies for sharia insurance products that are effective in attracting the interest of the millennial generation through social media. The research method used is a literature study to collect information about the characteristics of the millennial generation, consumer behavior and social media marketing strategies. The research results show that the millennial generation tends to be skeptical of financial products, but they are very connected tosocial media and are more receptive to information through recommendations from fellow users. Therefore, an effective sharia insurance product marketing strategy must focus on creating content that is informative, interesting and relevant to the needs andvalues of the millennial generation. Apart from that, collaborating with digital influencers and utilizing interactive features on social media platforms can also increase product appeal. This research contributes to understanding how to effectively reachthe millennial generation as a potential target market for sharia insurance products through social media.